Aluminum-based lead alloy / cobalt-doped carbon fiber powder-alpha-PbO2 composite positive grid and preparation method thereof

By using a composite structure of an aluminum-based lead alloy and a composite active layer of cobalt-doped carbon fiber powder-α-PbO2 in the positive electrode grid of the lead-acid battery, the problem of insufficient corrosion resistance and service life of the positive electrode grid in the prior art is solved, and higher tensile strength, conductive properties and cycle lengthening are achieved.

CN119920910AActive Publication Date: 2025-05-02KUNMING UNIV OF SCI & TECH +2

Patent Information

Application Number
CN202510090214.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The lack of composite positive electrode grids with low cost, high creep resistance, corrosion resistance and good mechanical properties in the prior art, resulting in insufficient service life of lead-acid batteries and low corrosion resistance under high temperature environments.

Method used

The aluminum-based lead alloy is used as the matrix, and the corrosion resistance and catalytic activity of the positive electrode grid are improved by doping the cobalt-encapsulated carbon fiber powder-α-PbO2 composite active layer. The composite structure includes an aluminum alloy matrix, a galvanized antimony layer, a nano-doped La2O3-nickel bottom layer, a Pb-Sn-Bi-Ag alloy intermediate layer and a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer.

Benefits of technology

It significantly reduces the weight of the battery, improves the tensile strength and conductivity, extends the cycle of lead-acid batteries, improves the corrosion resistance and catalytic activity of the battery, and meets the long-term and frequent charging and discharge needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920910A_ABST
    Figure CN119920910A_ABST
Patent Text Reader

Abstract

The invention relates to an aluminum-based lead alloy / cobalt-doped coated carbon fiber powder-alpha-PbO2 composite positive grid and a preparation method thereof, and belongs to the technical field of battery grids. The aluminum-based lead alloy / cobalt-doped coated carbon fiber powder-alpha-PbO2 composite positive plate grid sequentially comprises an aluminum alloy matrix, a zinc immersion antimony layer, a nanometer La2O3-doped nickel bottom layer, a Pb-Sn-Bi-Ag alloy middle layer and a porous cobalt-doped coated carbon fiber powder-alpha-PbO2 composite active layer from inside to outside. The catalytic activity of the electrode plate is improved by utilizing high conductivity and large bearing current intensity of aluminum, and the outer layer is doped with cobalt-coated carbon fiber powder-alpha-PbO2, so that the corrosion resistance of the positive grid can be improved, and the service life of the positive grid can be prolonged. Compared with a traditional lead alloy, the aluminum-based lead alloy composite positive plate grid has the advantages that the weight is reduced by more than 50%, the tensile strength is improved by 34%, and the conductivity is improved by more than 28%. Under the condition of 100% depth of discharge (DOD), the cycle period of a lead storage battery using the aluminum-based lead alloy anode grid is prolonged by 25%, and the long-term frequent charge and discharge requirements of a lead-acid energy storage battery can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum-based lead alloy / cobalt-doped carbon fiber powder-alpha-PbO2 composite positive electrode grid and a preparation method thereof, belonging to the technical field of battery grids. Background Art

[0002] Lead-carbon batteries have always been the key development direction of energy storage projects due to their high safety and high reliability without combustibles. However, due to their low capacity density, they are mainly used in small energy storage systems, and the research and development of ultra-large capacity pure lead-carbon batteries is imminent. The positive grid of ultra-large capacity pure lead-carbon batteries requires high injection pressure during processing because of the large number of lead bars, long length and thin diameter. The produced positive grid has a high failure rate and low efficiency.

[0003] In order to improve the problem of passive film and corrosion growth, many people have done a lot of research on alloy additives in recent years. Invention patent CN109518017A discloses a lead alloy for maintenance-free lead-acid battery positive plate grid and its preparation method. The battery made of the lead alloy described in the invention has a service life of more than 35% higher than that of the battery made of ordinary alloy in a high temperature environment, extending the service life of the battery under high temperature conditions. Invention patent CN 107881356 A discloses a silver alloy positive plate grid for lead-acid batteries and its preparation method. The battery made of the lead alloy described in the invention can solve the problems of severe intergranular corrosion and large passive film impedance, and improve the corrosion resistance of the plate grid alloy. Although the alloys prepared by the above invention patents have their own advantages, they still need to be improved in terms of comprehensive cost and performance such as low cost, high creep resistance, high corrosion resistance, and high mechanical properties.

[0004] Therefore, there is an urgent need to develop a low-cost composite positive electrode grid with high creep resistance, corrosion resistance and good mechanical properties to improve the comprehensive market competitiveness of lead-acid battery products. Summary of the invention

[0005] In view of the fact that there is no low-cost composite positive grid with high creep resistance, corrosion resistance and good mechanical properties in the prior art, the present invention provides an aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive grid and a preparation method thereof, which utilizes the high conductivity of aluminum and the large current intensity carried to improve the catalytic activity of the electrode plate. The outer layer of cobalt-doped carbon fiber powder-α-PbO2 can improve the corrosion resistance of the positive grid and extend the service life of the positive grid. Compared with traditional lead alloys, the aluminum-based lead alloy composite positive grid of the present invention not only reduces weight by more than 50%, but also increases tensile strength by 34% and conductivity by more than 28%. Under 100% depth of discharge (DOD) conditions, the cycle period of lead-acid batteries using aluminum-based lead alloy anode grids is extended by 25%, which can meet the long-term frequent charging and discharging needs of lead-acid energy storage batteries.

[0006] The invention discloses an aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid, which comprises, from the inside to the outside, an aluminum alloy substrate, a zinc-antimony impregnated layer 1, a nano-La2O3-doped nickel bottom layer 2, a Pb-Sn-Bi-Ag alloy middle layer 3 and a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4.

[0007] In terms of mass percentage, the aluminum alloy matrix contains 0.2-0.8% Ca, 0.01-0.2% Zr, 0.01-0.1% Ce, 0.01-0.2% Sc, 0.001-0.3% A1-5Ti-B, and the balance is Al;

[0008] In terms of mass percentage, Sb accounts for 5-10% in the zinc-antimony layer 1, and the remainder is Zn;

[0009] In terms of mass percentage, the La2O3 in the nano-La2O3-nickel bottom layer 2 accounts for 0.2-5%, and the balance is Ni;

[0010] In terms of mass percentage, the Pb-Sn-Bi-Ag alloy intermediate layer 3 contains 0.5-5.0% Sn, 0.1-1.0% Bi, 0.005-0.1% Ag, and the balance is Pb;

[0011] Calculated by mass percentage, the cobalt-coated carbon fiber powder in the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4 accounts for 0.5-5.0%, and the remainder is α-PbO2; calculated by mass percentage of the cobalt-coated carbon fiber powder, Co accounts for 5-20% in the cobalt-coated carbon fiber powder, and the remainder is carbon fiber.

[0012] Preferably, the aluminum alloy substrate is a plate-shaped structure, with a pattern pressed on the surface, the pattern depth is 0.05-0.5 mm, the pattern width is 0.05-0.3 mm, and the cross-sectional thickness is 0.5-6 mm;

[0013] The thickness of the zinc-antimony layer 1 is 0.5-3 μm; the thickness of the nano-La2O3-nickel bottom layer 2 is 3-8 μm; the thickness of the Pb-Sn-Bi-Ag alloy intermediate layer 3 is 0.5-4 mm; the thickness of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4 is 0.1-1.0 mm.

[0014] The preparation method of the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid comprises the following specific steps:

[0015] S1. Preparation of Zn-Sb layer for immersion plating of aluminum alloy grid: soaking the aluminum alloy grid substrate in an alkaline solution to remove oil, washing with deionized water and placing it in an alkaline zinc-antimony solution for a primary immersion plating reaction, washing with deionized water and placing it in an HNO3 solution for activation, washing with deionized water and placing it in an alkaline zinc-antimony solution for a secondary immersion plating reaction, and washing with deionized water to obtain an aluminum alloy grid with a Zn-Sb layer;

[0016] S2. Preparation of aluminum alloy grid doped with nano-La2O3-nickel bottom layer: an aluminum alloy grid with a Zn-Sb layer as a cathode and a pure nickel plate as an anode was plated in a neutral nickel plating solution, and the aluminum alloy grid doped with nano-La2O3-nickel bottom layer was obtained by washing with deionized water;

[0017] S3. Preparation of aluminum alloy grid Pb-Sn-Bi-Ag alloy intermediate layer: using the aluminum alloy grid doped with nano-La2O3-nickel bottom layer as the cathode and the lead-tin alloy plate as the anode, electrodepositing in a lead fluoroborate plating solution, and washing with deionized water to obtain an aluminum alloy grid with a Pb-Sn-Bi-Ag alloy intermediate layer;

[0018] S4. Preparation of porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer of aluminum alloy grid: The aluminum alloy grid with Pb-Sn-Bi-Ag alloy intermediate layer is subjected to surface sandblasting treatment, placed in a sodium hydroxide solution for alkaline dissolution treatment, and washed with deionized water to obtain a porous anode grid. The porous anode grid is used as the anode and the stainless steel plate is used as the cathode. Electrodeposition is carried out in an alkaline lead plating solution, and the aluminum alloy grid with a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer is obtained after washing with deionized water.

[0019] Preferably, the step S1. the method for preparing the aluminum alloy grid substrate comprises the following specific steps:

[0020] S11. According to the composition of the aluminum alloy matrix, pure aluminum ingots, electrolytic calcium, metal zirconium blocks, metal cerium blocks, metal scandium blocks and aluminum titanium boron filaments are mixed uniformly, placed in a vacuum melting furnace, evacuated, introduced with argon gas, induction heated at a temperature of 580-700°C until completely melted, and a refining agent ZnCl2-KCl is added, slag is removed, and casting is performed to obtain an aluminum alloy ingot; more preferably, based on the mass of the aluminum alloy ingot being 100%, the amount of the refining agent ZnCl2 added is 1-4%, and the amount of KCl added is 1-4%; more preferably, the temperature of the casting mold is 100-200°C;

[0021] S12. The aluminum alloy ingot is placed at a temperature of 180-250°C for heat treatment for 0.5-2h, hot rolled with a deformation of 60-80%, cooled to room temperature and then aged for more than 24h, annealed at a temperature of 80-120°C for 1-3h after rolling and embossing, and cut into the required aluminum alloy grid size under the protection of laser argon to obtain an aluminum alloy grid substrate.

[0022] Preferably, the alkaline solution in step S1 is a NaOH-Na2CO3 mixed solution, wherein NaOH

[0023] 10~40g / L, Na2CO3 20~40g / L;

[0024] The alkaline zinc antimony solution contains 200-400 g / L NaOH, 60-80 g / L ZnO, 30-80 g / L potassium antimony tartrate, 0.5-2 g / L FeCl3, and 1-3 g / L NaNO3;

[0025] The mass concentration of HNO3 solution is 20-50%.

[0026] Preferably, the soaking degreasing temperature in step S1 is 60-80° C. and the time is 1-5 min;

[0027] The temperature of the primary immersion plating reaction is 30-50°C and the time is 10-60S;

[0028] Activation time is 10 to 60 seconds;

[0029] The temperature of the secondary immersion plating reaction is 30-50°C and the time is 10-30S.

[0030] Preferably, the neutral nickel plating solution in step S2 contains 100-300 g / L nickel sulfate, 10-30 g / L nickel chloride, 100-300 g / L citric acid, 10-60 g / L boric acid, and 5-20 g / L nano La2O3 powder; the pH of the neutral nickel plating solution is 5-7;

[0031] The cathode current density of composite plating is 1~5A / dm 2 , temperature is 40-60℃, time is 5-20min.

[0032] Preferably, the lead fluoroborate plating solution in step S3 contains 100-300 g / L lead acetate, 100-200 g / L fluoroboric acid, 10-30 g / L boric acid, 10-50 g / L stannous fluoroborate, 2-8 g / L bismuth oxide, and 1-3 g / L silver oxide; the pH value of the lead fluoroborate plating solution is 1-2;

[0033] Anode current density of electrodeposition is 1~5A / dm 2 , temperature is 30~50℃, time is 12~24h.

[0034] Preferably, the concentration of the sodium hydroxide solution in step S4 is 40 to 100 g / L, the temperature of the alkali treatment is 40 to 60° C., and the time is 4 to 8 hours;

[0035] Step S4. The alkaline lead plating solution contains 30-60 g / L lead oxide, 100-200 g / L sodium hydroxide, 100-300 g / L potassium sodium tartrate, 10-40 g / L sodium ethylenediaminetetraacetate, and 4-16 g / L cobalt-coated carbon fiber powder;

[0036] Anode current density of electrodeposition is 1~3A / dm 2 , temperature is 40-60℃, time is 4-8h.

[0037] Preferably, the method for preparing the cobalt-coated carbon fiber powder comprises the following specific steps:

[0038] S41. The carbon fiber was sequentially subjected to calcination to remove the glue, roughening with nitric acid solution, sensitization with stannous chloride-hydrochloric acid, and activation with colloidal silver citrate to obtain pretreated carbon fiber;

[0039] S42. The pretreated carbon fiber is placed in a cobalt sulfate plating solution for chemical cobalt plating to obtain a cobalt-coated carbon fiber powder; the cobalt sulfate plating solution contains 5-20 g / L cobalt sulfate, 5-30 g / L ethylenediaminetetraacetic acid, 5-20 g / L sodium hydroxide, 0.2-10 mg / L thiourea, and 5-20 ml / L formaldehyde.

[0040] More preferably, the S41. carbon fiber powder has a major diameter of 10 to 100 μm and a minor diameter of 0.1 to 5 μm.

[0041] More preferably, the temperature of the baking degumming treatment in S41 is 300-500°C, and the time is 10-30min; the mass concentration of the nitric acid solution is 10-30%, and the roughening time is 5-10min; the stannous chloride-hydrochloric acid contains 5-20g / L stannous chloride and 5-20ml / L hydrochloric acid, and the sensitization time is 5-10min; the concentration of the silver citrate colloid is 5-20g / L, and the activation time is 1-5min;

[0042] More preferably, the temperature of S42. chemical cobalt plating is 40-70° C. and the time is 10-60 min.

[0043] The beneficial effects of the present invention are:

[0044] (1) Since aluminum has a low density, higher strength than lead alloy, and good electrical conductivity, the present invention uses aluminum alloy aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid as the substrate, which can significantly reduce the weight of the battery and improve the tensile strength. The electrical conductivity of the aluminum-based composite lead positive electrode grid is better than that of the traditional lead alloy battery positive electrode material, which helps to improve the battery's charge and discharge efficiency; and the cost of aluminum is low, which can reduce the production cost of the battery positive electrode material;

[0045] (2) The aluminum-based lead composite material of the present invention has stable electrochemical performance, and can reduce the positive electrode oxygen evolution overpotential and increase the anode electrocatalytic performance, thereby promoting the conversion of active substances, improving utilization, reducing water loss, and extending the battery cycle life;

[0046] (3) The battery using the aluminum-based composite lead positive grid of the present invention has improved rate discharge performance and active material utilization, and significantly reduces the internal resistance of the lead-acid battery by reducing the physical resistance and electrochemical reaction impedance of the plate;

[0047] (4) The transition layer (zinc-antimony impregnation layer and nano-La2O3-nickel base layer) of the present invention has a certain leveling effect, which can effectively repair the surface of the aluminum substrate, so that the thickness of the prepared lead plating layer is uniform; the two form a metallurgical bond to strengthen the bonding force between the aluminum substrate and the lead alloy;

[0048] (5) The present invention utilizes the good conductivity of Ag to firmly bond the Pb-Sn-Bi-Ag alloy intermediate layer with the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer, thereby reducing the interface resistance. The cobalt-doped carbon fiber powder-α-PbO2 composite active layer has good activity and strong corrosion resistance, which greatly improves the corrosion resistance and activity of the positive electrode grid. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a schematic diagram of the structure of an aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid;

[0050] Figure 2 for Figure 1 AA cross-sectional diagram of ;

[0051] In the figure: 1- zinc-antimony impregnation layer, 2- nano-La2O3-nickel bottom layer, 3-Pb-Sn-Bi-Ag alloy middle layer, 4- porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer;

[0052] Figure 3 This is a graph showing the cycle performance of a lead-acid battery using the aluminum-based lead alloy positive electrode grid of Example 3. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0054] Summary of the Invention

[0055] A composite positive electrode grid of aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 (see Figure 1 and 2), from inside to outside, it is an aluminum alloy substrate, a zinc-antimony impregnated layer 1, a nano-La2O3-nickel bottom layer 2, a Pb-Sn-Bi-Ag alloy intermediate layer 3, and a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4;

[0056] In terms of mass percentage, the aluminum alloy matrix contains 0.2-0.8% Ca, 0.01-0.2% Zr, 0.01-0.1% Ce, 0.01-0.2% Sc, 0.001-0.3% A1-5Ti-B, and the balance is Al;

[0057] In terms of mass percentage, Sb accounts for 5-10% in the zinc-antimony layer 1, and the remainder is Zn;

[0058] In terms of mass percentage, the La2O3 in the nano-La2O3-nickel bottom layer 2 accounts for 0.2-5%, and the balance is Ni;

[0059] In terms of mass percentage, the Pb-Sn-Bi-Ag alloy intermediate layer 3 contains 0.5-5.0% Sn, 0.1-1.0% Bi, 0.005-0.1% Ag, and the balance is Pb;

[0060] In terms of mass percentage, the cobalt-coated carbon fiber powder in the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4 accounts for 0.5-5.0%, and the remainder is α-PbO2; in terms of mass percentage of the cobalt-coated carbon fiber powder, Co accounts for 5-20% of the cobalt-coated carbon fiber powder, and the remainder is carbon fiber;

[0061] The aluminum alloy substrate is a plate-shaped structure, with a pattern pressed on the surface, the pattern depth is 0.05-0.5mm, the pattern width is 0.05-0.3mm, and the cross-sectional thickness is 0.5-6mm;

[0062] The thickness of the zinc-antimony layer 1 is 0.5-3 μm; the thickness of the nano-La2O3-nickel bottom layer 2 is 3-8 μm; the thickness of the Pb-Sn-Bi-Ag alloy intermediate layer 3 is 0.5-4 mm; the thickness of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4 is 0.1-1.0 mm.

[0063] The preparation method of the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid comprises the following specific steps:

[0064] S1. Preparation of Zn-Sb layer of aluminum alloy grid: soaking the aluminum alloy grid substrate in an alkaline solution to remove oil, washing with deionized water and placing it in an alkaline zinc antimony solution for a first immersion plating reaction, washing with deionized water and placing it in an HNO3 solution for activation, washing with deionized water and placing it in an alkaline zinc antimony solution for a second immersion plating reaction, and washing with deionized water to obtain an aluminum alloy grid with a Zn-Sb layer; the alkaline solution is a NaOH-Na2CO3 mixed solution, wherein the alkaline solution contains 10-40 g / L NaOH and 10-40 g / L Na2CO3.

[0065] 20~40g / L; the alkaline zinc antimony solution contains 200~400g / L NaOH, 60~80g / L ZnO, 30~80g / L potassium antimony tartrate, 0.5~2g / L FeCl3, 1~3g / L NaNO3; the mass concentration of HNO3 solution is 20~50%;

[0066] Preferably, the immersion degreasing temperature is 60-80°C, and the time is 1-5 minutes; the temperature of the first immersion plating reaction is 30-50°C, and the time is 10-60 seconds; the activation time is 10-60 seconds; the temperature of the second immersion plating reaction is 30-50°C, and the time is 10-30 seconds;

[0067] The step S1. a method for preparing an aluminum alloy grid substrate comprises the following specific steps:

[0068] S11. According to the composition of the aluminum alloy matrix, pure aluminum ingots, electrolytic calcium, metal zirconium blocks, metal cerium blocks, metal scandium blocks and aluminum titanium boron filaments are mixed uniformly, placed in a vacuum melting furnace, evacuated, introduced with argon gas, induction heated at a temperature of 580-700°C until completely melted, and a refining agent ZnCl2-KCl is added, slag is removed, and casting is performed to obtain an aluminum alloy ingot; more preferably, based on the mass of the aluminum alloy ingot being 100%, the amount of the refining agent ZnCl2 added is 1-4%, and the amount of KCl added is 1-4%; more preferably, the temperature of the casting mold is 100-200°C;

[0069] S12. The aluminum alloy ingot is placed at a temperature of 180 to 250 ° C for 0.5 to 2 hours, hot rolled with a deformation of 60 to 80%, cooled to room temperature, and then aged for more than 24 hours. After rolling and embossing, it is annealed at a temperature of 80 to 120 ° C for 1 to 3 hours, and cut into the required aluminum alloy grid size under the protection of laser argon gas to obtain an aluminum alloy grid substrate;

[0070] S2. Preparation of aluminum alloy grid doped with nano-La2O3-nickel bottom layer: using an aluminum alloy grid plated with a Zn-Sb layer as a cathode and a pure nickel plate as an anode, composite plating is performed in a neutral nickel plating solution, and the aluminum alloy grid doped with nano-La2O3-nickel bottom layer is obtained by washing with deionized water; the neutral nickel plating solution contains 100-300 g / L nickel sulfate, 10-30 g / L nickel chloride, 100-300 g / L citric acid, 10-60 g / L boric acid, and 5-20 g / L nano-La2O3 powder; the pH of the neutral nickel plating solution is 5-7; the cathode current density of the composite plating is 1-5 A / dm 2 , temperature is 40~60℃, time is 5~20min;

[0071] S3. Preparation of aluminum alloy grid with Pb-Sn-Bi-Ag alloy intermediate layer: using an aluminum alloy grid doped with nano-La2O3-nickel bottom layer as a cathode and a lead-tin alloy plate as an anode, electroplating in a lead fluoroborate plating solution, and washing with deionized water to obtain an aluminum alloy grid with a Pb-Sn-Bi-Ag alloy intermediate layer; the lead fluoroborate plating solution contains 100-300 g / L lead acetate, 100-200 g / L fluoroboric acid, 10-30 g / L boric acid, 10-50 g / L stannous fluoroborate, 2-8 g / L bismuth oxide, and 1-3 g / L silver oxide; the pH value of the lead fluoroborate plating solution is 1-2; the anode current density of the electroplating is 1-5 A / dm 2 , the temperature is 30-50℃, the time is 12-24h;

[0072] S4. Preparation of porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer of aluminum alloy grid: the aluminum alloy grid with Pb-Sn-Bi-Ag alloy intermediate layer is subjected to surface sandblasting treatment, placed in sodium hydroxide solution for alkaline dissolution treatment, washed with deionized water to obtain a porous anode grid, the porous anode grid is used as anode, the stainless steel plate is used as cathode, and electrodeposition is performed in an alkaline lead plating solution, and after washing with deionized water, an aluminum alloy grid with a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer is obtained; the concentration of the sodium hydroxide solution is 40-100 g / L, the temperature of the alkaline dissolution treatment is 40-60°C, and the time is 4-8 h; the alkaline lead plating solution contains 30-60 g / L lead oxide, 100-200 g / L sodium hydroxide, 100-300 g / L potassium sodium tartrate, 10-40 g / L sodium ethylenediaminetetraacetic acid, and 4-16 g / L cobalt-coated carbon fiber powder; the anode current density of the electrodeposition is 1-3 A / dm 2 , the temperature is 40-60℃, the time is 4-8h;

[0073] Preferably, the method for preparing the cobalt-coated carbon fiber powder comprises the following specific steps:

[0074] S41. The carbon fiber is sequentially subjected to calcination degumming treatment, nitric acid solution coarsening, stannous chloride-hydrochloric acid sensitization, and silver citrate colloid activation to obtain pretreated carbon fiber; the carbon fiber powder has a major diameter of 10 to 100 μm and a minor diameter of 0.1 to 5 μm; the calcination degumming treatment temperature is 300 to 500°C and the time is 10 to 30 min; the nitric acid solution mass concentration is 10 to 30%, and the coarsening time is 5 to 10 min; the stannous chloride-hydrochloric acid contains 5 to 20 g / L stannous chloride and 5 to 20 ml / L hydrochloric acid, and the sensitization time is 5 to 10 min; the silver citrate colloid concentration is 5 to 20 g / L, and the activation time is 1 to 5 min;

[0075] S42. The pretreated carbon fiber is placed in a cobalt sulfate plating solution for chemical cobalt plating to obtain cobalt-coated carbon fiber powder; the cobalt sulfate plating solution contains 5-20 g / L cobalt sulfate, 5-30 g / L ethylenediaminetetraacetic acid, 5-20 g / L sodium hydroxide, 0.2-10 mg / L thiourea, and 5-20 ml / L formaldehyde; the temperature of the chemical cobalt plating is 40-70°C, and the time is 10-60 min.

[0076] Example 1: A composite positive electrode grid of aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 (see Figure 1 and 2 ), from inside to outside, it is an aluminum alloy substrate, a zinc-antimony impregnated layer 1, a nano-La2O3-nickel bottom layer 2, a Pb-Sn-Bi-Ag alloy intermediate layer 3, and a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4;

[0077] In terms of mass percentage, the aluminum alloy matrix contains 0.2% Ca, 0.01% Zr, 0.01% Ce, 0.01% Sc, 0.001% A1-5Ti-B, and the balance is A1;

[0078] In terms of mass percentage, Sb accounts for 5% of the zinc-antimony layer 1, and the remainder is Zn;

[0079] In terms of mass percentage, the La2O3 in the nano-La2O3-nickel bottom layer 2 accounts for 0.2%, and the balance is Ni;

[0080] In terms of mass percentage, the Pb-Sn-Bi-Ag alloy intermediate layer 3 contains 0.5% Sn, 0.1% Bi,

[0081] 0.005% Ag, the balance is Pb;

[0082] In terms of mass percentage, the cobalt-coated carbon fiber powder accounts for 0.5% of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4, and the remainder is α-PbO2; in terms of mass percentage of the cobalt-coated carbon fiber powder, Co accounts for 5% of the cobalt-coated carbon fiber powder, and the remainder is carbon fiber;

[0083] The aluminum alloy substrate is a plate-shaped structure, with a pattern pressed on the surface, the pattern depth is 0.05mm, the pattern width is 0.05mm, and the cross-sectional thickness is 0.5mm;

[0084] The thickness of the zinc-antimony layer 1 is 0.5 μm; the thickness of the nano-La2O3-nickel bottom layer 2 is 3 μm; the thickness of the Pb-Sn-Bi-Ag alloy intermediate layer 3 is 0.5 mm; the thickness of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4 is 0.1 mm;

[0085] The preparation method of the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid comprises the following specific steps:

[0086] S1. Preparation of Zn-Sb layer for aluminum alloy grid: Place the aluminum alloy grid substrate in an alkaline solution (NaOH-Na2CO3 mixed solution, NaOH 10g / L, Na2CO3 20g / L), soak and degrease at 60°C for 1min, wash with deionized water and place in an alkaline zinc antimony solution, perform a primary immersion plating reaction at 30°C for 10S, wash with deionized water and place in a 20% HNO3 solution for activation for 10S, wash with deionized water and place in an alkaline zinc antimony solution, perform a secondary immersion plating reaction at 30°C for 10S, and wash with deionized water to obtain an aluminum alloy grid with Zn-Sb layer; the alkaline zinc antimony solution contains 200g / LNaOH, 60g / L ZnO, 30g / L potassium antimony tartrate, 0.5g / L FeCl3, and 1g / L NaNO3;

[0087] The step S1. a method for preparing an aluminum alloy grid substrate comprises the following specific steps:

[0088] S11. According to the composition of the aluminum alloy matrix, pure aluminum ingots, electrolytic calcium, metal zirconium blocks, metal cerium blocks, metal scandium blocks and aluminum titanium boron filaments are mixed uniformly, placed in a vacuum melting furnace, evacuated, argon gas is introduced, and electromagnetic induction heating is performed at a temperature of 580°C until completely melted, and a refining agent ZnCl2-KCl is added (based on the mass of the aluminum alloy ingot as 100%, the amount of refining agent ZnCl2 added is 1%, and the amount of KCl added is 1%), slag is removed, and casting is performed (the temperature of the mold is 100°C) to obtain an aluminum alloy ingot;

[0089] S12. The aluminum alloy ingot is heat treated at 180°C for 0.5h, hot rolled with a deformation amount of 60%, cooled to room temperature and aged for 24h, annealed at 80°C for 1h after rolling and embossing, and cut into the desired aluminum alloy grid size under laser argon protection to obtain an aluminum alloy grid substrate;

[0090] S2. Preparation of aluminum alloy grid doped with nano-La2O3-nickel bottom layer: The aluminum alloy grid with Zn-Sb layer was used as cathode and the pure nickel plate was used as anode. In a neutral nickel plating solution, the cathode current density was 1A / dm 2 , composite plating is performed at a temperature of 40° C. for 5 minutes, and the aluminum alloy grid doped with nano-La2O3-nickel bottom layer is obtained by washing with deionized water; the neutral nickel plating solution contains 100 g / L nickel sulfate, 10 g / L nickel chloride, 100 g / L citric acid, 10 g / L boric acid, and 5 g / L nano-La2O3 powder; the pH of the neutral nickel plating solution is 7;

[0091] S3. Preparation of aluminum alloy grid Pb-Sn-Bi-Ag alloy intermediate layer: The aluminum alloy grid doped with nano-La2O3-nickel bottom layer is used as the cathode, and the lead-tin alloy plate is used as the anode. In the lead fluoroborate plating solution, the stirring rate is 100 rpm and the anode current density is 1A / dm 2 , electroplating at a temperature of 30° C. for 12 hours, and washing with deionized water to obtain an aluminum alloy grid with a Pb-Sn-Bi-Ag alloy intermediate layer; the lead fluoroborate plating solution contains 100 g / L lead acetate, 100 g / L fluoroboric acid, 10 g / L boric acid, 10 g / L stannous fluoroborate, 2 g / L bismuth oxide, and 1 g / L silver oxide; the pH value of the lead fluoroborate plating solution is 2;

[0092] S4. Preparation of porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer of aluminum alloy grid: The aluminum alloy grid with Pb-Sn-Bi-Ag alloy intermediate layer was sandblasted on the surface (sand is silica particles with a particle size of 0.5 mm), placed in a sodium hydroxide solution with a concentration of 40 g / L, and alkaline dissolved for 4 h at a temperature of 40 ° C. After washing with deionized water, a porous anode grid was obtained. The porous anode grid was used as the anode and the stainless steel plate was used as the cathode. In an alkaline lead plating solution, at an anode current density of 1 A / dm 2 , the temperature is 40 ℃ for 4h, and after washing with deionized water, a porous aluminum alloy grid with cobalt-doped carbon fiber powder-α-PbO2 composite active layer is obtained; the alkaline lead plating solution contains 30g / L lead oxide, 100g / L sodium hydroxide, 100g / L potassium sodium tartrate, 10g / L sodium ethylenediaminetetraacetate, and 4g / L cobalt-doped carbon fiber powder;

[0093] The method for preparing the cobalt-coated carbon fiber powder comprises the following specific steps:

[0094] S41. Carbon fibers (long diameter of 10 μm, short diameter of 0.1 μm) were sequentially subjected to calcination at 300°C for degumming, roughening with a 10% nitric acid solution for 5 min, sensitization with stannous chloride-hydrochloric acid (5 g / L stannous chloride, 5 ml / L hydrochloric acid) for 5 min, and activation with 5 g / L silver citrate colloid for 1 min to obtain pretreated carbon fibers;

[0095] S42. The pretreated carbon fiber is placed in a cobalt sulfate plating solution and chemically plated with cobalt at a temperature of 40 ° C for 10 min to obtain a cobalt-coated carbon fiber powder; the cobalt sulfate plating solution contains 5g / L cobalt sulfate, 5g / L ethylenediaminetetraacetic acid, 5g / L sodium hydroxide, 0.2mg / L thiourea, 5ml / L formaldehyde;

[0096] Compared with the traditional lead alloy positive electrode grid, the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid of this embodiment has a 50% lighter weight, a 34% higher tensile strength, and a 28% higher conductivity.

[0097] Prepare and assemble lead-acid batteries according to conventional methods: make pole plates through grid casting, lead paste preparation and paste coating processes; weigh and group the pole plates, and alternately wrap the positive and negative pole plates with separators; weld the assembled pole plates to form pole groups; put the pole groups into clean battery slots, inject glue to seal the battery shell, add the prepared electrolyte from the acid injection port, and seal the acid injection port after the battery is formed; finally, perform performance tests on the assembled batteries to ensure the quality and performance of the batteries;

[0098] Formation treatment: After injecting the electrolyte, the battery is left to stand for a period of time to allow the diaphragm and the plate to fully absorb the acid, and then activated by multiple charge and discharge with a large current. After activation, the battery is initially ready for use.

[0099] Capacity test: The actual capacity of the battery is measured and calculated by constant current discharge. The discharge current is generally 0.1C, and the battery is discharged for 10 hours to the termination voltage, such as 1.8V. The capacity test can accurately evaluate whether the battery's energy storage capacity meets the design requirements.

[0100] Internal resistance test: Use an electrochemical workstation or battery test system to measure the AC impedance of the battery. The internal resistance test is usually performed in different frequency ranges to obtain the impedance spectrum of the battery. The internal resistance directly affects the charge and discharge efficiency and thermal management performance of the battery.

[0101] Rate performance test: Test the battery at different discharge rates, such as 0.05C, 0.1C, 0.5C, 1C, 2C, etc. Rate performance test can evaluate the performance of the battery at different discharge rates, which is of guiding significance for the applicability of the battery in different application scenarios;

[0102] Cycle life test: Perform multiple charge and discharge cycles on the battery, and record the capacity, voltage, internal resistance and other parameters of each cycle. Cycle life test can evaluate the performance stability and life span of the battery during long-term use. Usually, a fixed discharge value and discharge depth are set to detect the number of cycles, such as setting the cycle discharge conditions of 0.1C and 70% DOD (discharge depth) to observe the changing trend of battery performance;

[0103] Under the condition of 70% depth of discharge (DOD), the cycle period of the lead-acid battery using the aluminum-based lead alloy anode grid of this embodiment is extended by 15%, which can meet the long-term frequent charging and discharging requirements of the lead-acid energy storage battery.

[0104] Example 2: A composite positive electrode grid of aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 (see Figure 1 and 2 ), from inside to outside, it is an aluminum alloy substrate, a zinc-antimony impregnated layer 1, a nano-La2O3-nickel bottom layer 2, a Pb-Sn-Bi-Ag alloy intermediate layer 3, and a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4;

[0105] In terms of mass percentage, the aluminum alloy matrix contains 0.8% Ca, 0.2% Zr, 0.1% Ce, 0.2% Sc, 0.3% A1-5Ti-B, and the balance is Al;

[0106] In terms of mass percentage, Sb accounts for 10% of the zinc-antimony layer 1, and the remainder is Zn;

[0107] In terms of mass percentage, the La2O3 in the nano-doped La2O3-nickel bottom layer 2 accounts for 5%, and the balance is Ni;

[0108] In terms of mass percentage, the Pb-Sn-Bi-Ag alloy intermediate layer 3 contains 5.0% Sn, 1.0% Bi, 0.1% Ag, and the balance is Pb;

[0109] In terms of mass percentage, the cobalt-coated carbon fiber powder accounts for 5.0% of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4, and the remainder is α-PbO2; in terms of mass percentage of the cobalt-coated carbon fiber powder, Co accounts for 20% of the cobalt-coated carbon fiber powder, and the remainder is carbon fiber;

[0110] The aluminum alloy substrate is a plate-shaped structure, with a pattern pressed on the surface, the pattern depth is 0.5mm, the pattern width is 0.3mm, and the cross-sectional thickness is 6mm;

[0111] The thickness of the zinc-antimony layer 1 is 3 μm; the thickness of the nano-La2O3-nickel bottom layer 2 is 8 μm; the thickness of the Pb-Sn-Bi-Ag alloy intermediate layer 3 is 4 mm; the thickness of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4 is 1.0 mm;

[0112] The preparation method of the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid comprises the following specific steps:

[0113] S1. Preparation of Zn-Sb layer for aluminum alloy grid: Place the aluminum alloy grid substrate in an alkaline solution (NaOH-Na2CO3 mixed solution, NaOH 40g / L, Na2CO3 40g / L), soak and degrease at 80°C for 5min, wash with deionized water and place in an alkaline zinc antimony solution, perform a primary immersion plating reaction at 50°C for 60S, wash with deionized water and place in a 50% HNO3 solution for activation for 60S, wash with deionized water and place in an alkaline zinc antimony solution, perform a secondary immersion plating reaction at 50°C for 30S, and wash with deionized water to obtain an aluminum alloy grid with Zn-Sb layer; the alkaline zinc antimony solution contains 400g / LNaOH, 80g / L ZnO, 80g / L potassium antimony tartrate, 2g / L FeCl3, and 3g / L NaNO3;

[0114] The step S1. a method for preparing an aluminum alloy grid substrate comprises the following specific steps:

[0115] S11. According to the composition of the aluminum alloy matrix, pure aluminum ingots, electrolytic calcium, metal zirconium blocks, metal cerium blocks, metal scandium blocks and aluminum titanium boron filaments are mixed uniformly, placed in a vacuum melting furnace, evacuated, argon gas is introduced, and electromagnetic induction heating is performed at a temperature of 700°C until it is completely melted, and a refining agent ZnCl2-KCl is added (based on the mass of the aluminum alloy ingot as 100%, the amount of refining agent ZnCl2 added is 4%, and the amount of KCl added is 4%), slag is removed, and casting is performed (the temperature of the mold is 200°C) to obtain an aluminum alloy ingot;

[0116] S12. The aluminum alloy ingot is heat treated at 250°C for 2h, hot rolled with 80% deformation, cooled to room temperature and aged for 25h, annealed at 120°C for 3h after rolling and embossing, and cut into the desired aluminum alloy grid size under laser argon protection to obtain an aluminum alloy grid substrate;

[0117] S2. Preparation of aluminum alloy grid doped with nano-La2O3-nickel bottom layer: The aluminum alloy grid with Zn-Sb layer was used as cathode and the pure nickel plate was used as anode. In a neutral nickel plating solution, the cathode current density was 4A / dm 2 , performing composite plating at a temperature of 60° C. for 20 minutes, and washing with deionized water to obtain an aluminum alloy grid doped with a nano-La2O3-nickel bottom layer; the neutral nickel plating solution contains 300 g / L nickel sulfate, 30 g / L nickel chloride, 300 g / L citric acid, 60 g / L boric acid, and 20 g / L nano-La2O3 powder; the pH of the neutral nickel plating solution is 5;

[0118] S3. Preparation of aluminum alloy grid Pb-Sn-Bi-Ag alloy intermediate layer: The aluminum alloy grid doped with nano-La2O3-nickel bottom layer was used as the cathode and the lead-tin alloy plate was used as the anode. In the lead fluoroborate plating solution, the stirring rate was 300 rpm and the anode current density was 5 A / dm 2 , electroplating at a temperature of 50° C. for 24 hours, and washing with deionized water to obtain an aluminum alloy grid with a Pb-Sn-Bi-Ag alloy intermediate layer; the lead fluoroborate plating solution contains 300 g / L lead acetate, 200 g / L fluoroboric acid, 30 g / L boric acid, 50 g / L stannous fluoroborate, 8 g / L bismuth oxide, and 3 g / L silver oxide; the pH value of the lead fluoroborate plating solution is 1;

[0119] S4. Preparation of porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer of aluminum alloy grid: The aluminum alloy grid with Pb-Sn-Bi-Ag alloy intermediate layer was sandblasted on the surface (the sand was silica particles with a particle size of 4 mm), placed in a sodium hydroxide solution with a concentration of 100 g / L, and alkaline dissolved for 8 h at a temperature of 60°C. After washing with deionized water, a porous anode grid was obtained. The porous anode grid was used as the anode and the stainless steel plate was used as the cathode. In an alkaline lead plating solution, the stirring rate was 600 rpm and the anode current density was 3 A / dm 2 , the temperature is 60 ℃ for electrodeposition for 8 hours, and after washing with deionized water, a porous aluminum alloy grid with cobalt-doped carbon fiber powder-α-PbO2 composite active layer is obtained; the alkaline lead plating solution contains 60g / L lead oxide, 200g / L sodium hydroxide, 300g / L potassium sodium tartrate, 40g / L sodium ethylenediaminetetraacetate, and 16g / L cobalt-doped carbon fiber powder;

[0120] The method for preparing the cobalt-coated carbon fiber powder comprises the following specific steps:

[0121] S41. Carbon fibers (long diameter of 100 μm, short diameter of 5 μm) were subjected to calcination at 500°C for degumming, roughening with a 30% nitric acid solution for 10 min, sensitization with stannous chloride-hydrochloric acid (20 g / L stannous chloride, 20 ml / L hydrochloric acid) for 10 min, and activation with 20 g / L silver citrate colloid for 5 min to obtain pretreated carbon fibers;

[0122] S42. The pretreated carbon fiber is placed in a cobalt sulfate plating solution and chemically plated with cobalt for 60 min at a temperature of 70 ° C to obtain a cobalt-coated carbon fiber powder; the cobalt sulfate plating solution contains 20 g / L cobalt sulfate, 30 g / L ethylenediaminetetraacetic acid, 20 g / L sodium hydroxide, 10 mg / L thiourea, 20 ml / L formaldehyde;

[0123] Compared with the traditional lead alloy positive electrode grid, the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid of this embodiment has a 53% lighter weight, a 37% higher tensile strength, and a 30% higher conductivity.

[0124] Under the condition of 70% depth of discharge (DOD), the cycle period of the lead-acid battery using the aluminum-based lead alloy anode grid of this embodiment is extended by 20%, which can meet the long-term frequent charging and discharging requirements of the lead-acid energy storage battery.

[0125] Example 3: A composite positive electrode grid of aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 (see Figure 1 and 2 ), from inside to outside, it is an aluminum alloy substrate, a zinc-antimony impregnated layer 1, a nano-La2O3-nickel bottom layer 2, a Pb-Sn-Bi-Ag alloy intermediate layer 3, and a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4;

[0126] In terms of mass percentage, the aluminum alloy matrix contains 0.4% Ca, 0.1% Zr, 0.05% Ce, 0.1% Sc, 0.15% A1-5Ti-B, and the balance is A1;

[0127] In terms of mass percentage, Sb accounts for 7% of the zinc-antimony layer 1, and the remainder is Zn;

[0128] In terms of mass percentage, the La2O3 in the nano-La2O3-nickel bottom layer 2 accounts for 2.5%, and the balance is Ni;

[0129] In terms of mass percentage, the Pb-Sn-Bi-Ag alloy intermediate layer 3 contains 2.7% Sn, 0.5% Bi, 0.05% Ag, and the balance is Pb;

[0130] In terms of mass percentage, the cobalt-coated carbon fiber powder accounts for 2.8% of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4, and the remainder is α-PbO2; in terms of mass percentage of the cobalt-coated carbon fiber powder, Co accounts for 12% of the cobalt-coated carbon fiber powder, and the remainder is carbon fiber;

[0131] The aluminum alloy substrate is a plate-shaped structure, with a pattern pressed on the surface, the pattern depth is 0.25mm, the pattern width is 0.15mm, and the cross-sectional thickness is 3mm;

[0132] The thickness of the zinc-antimony layer 1 is 1.8 μm; the thickness of the nano-La2O3-nickel bottom layer 2 is 6 μm; the thickness of the Pb-Sn-Bi-Ag alloy intermediate layer 3 is 2 mm; the thickness of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer 4 is 0.5 mm;

[0133] The preparation method of the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid comprises the following specific steps:

[0134] S1. Preparation of Zn-Sb layer for aluminum alloy grid: Place the aluminum alloy grid substrate in an alkaline solution (NaOH-Na2CO3 mixed solution, NaOH 25g / L, Na2CO3 30g / L), soak and degrease at 70°C for 3min, wash with deionized water and place in an alkaline zinc antimony solution, perform a primary immersion plating reaction at 40°C for 30S, wash with deionized water and place in a 35% HNO3 solution for activation for 30S, wash with deionized water and place in an alkaline zinc antimony solution, perform a secondary immersion plating reaction at 40°C for 20S, and wash with deionized water to obtain an aluminum alloy grid with Zn-Sb layer; the alkaline zinc antimony solution contains 300g / LNaOH, 70g / L ZnO, 50g / L potassium antimony tartrate, 1.2g / L FeCl3, and 2g / L NaNO3;

[0135] The step S1. a method for preparing an aluminum alloy grid substrate comprises the following specific steps:

[0136] S11. According to the composition of the aluminum alloy matrix, pure aluminum ingots, electrolytic calcium, metal zirconium blocks, metal cerium blocks, metal scandium blocks and aluminum titanium boron filaments are mixed uniformly, placed in a vacuum melting furnace, evacuated, argon gas is introduced, and electromagnetic induction heating is performed at a temperature of 650°C until it is completely melted, and a refining agent ZnCl2-KCl is added (based on the mass of the aluminum alloy ingot as 100%, the amount of refining agent ZnCl2 added is 2%, and the amount of KCl added is 2%), slag is removed, and casting (the temperature of the mold is 150°C) is performed to obtain an aluminum alloy ingot;

[0137] S12. The aluminum alloy ingot is heat treated at 210°C for 1 hour, hot rolled with a deformation amount of 70%, cooled to room temperature and aged for 26 hours, annealed at 100°C for 2 hours after rolling and embossing, and cut into the desired aluminum alloy grid size under laser argon protection to obtain an aluminum alloy grid substrate;

[0138] S2. Preparation of aluminum alloy grid doped with nano-La2O3-nickel bottom layer: The aluminum alloy grid with Zn-Sb layer was used as cathode and the pure nickel plate was used as anode. In a neutral nickel plating solution, the cathode current density was 2A / dm 2 , composite plating is performed at a temperature of 50° C. for 12 minutes, and the aluminum alloy grid doped with nano-La2O3-nickel bottom layer is obtained by washing with deionized water; the neutral nickel plating solution contains 200 g / L nickel sulfate, 20 g / L nickel chloride, 200 g / L citric acid, 30 g / L boric acid, and 13 g / L nano-La2O3 powder; the pH of the neutral nickel plating solution is 6;

[0139] S3. Preparation of aluminum alloy grid Pb-Sn-Bi-Ag alloy intermediate layer: The aluminum alloy grid doped with nano-La2O3-nickel bottom layer is used as the cathode, and the lead-tin alloy plate is used as the anode. In the lead fluoroborate plating solution, the stirring rate is 200 rpm and the anode current density is 3A / dm 2 , electroplating at a temperature of 40° C. for 18 hours, and washing with deionized water to obtain an aluminum alloy grid with a Pb-Sn-Bi-Ag alloy intermediate layer; the lead fluoroborate plating solution contains 200 g / L lead acetate, 150 g / L fluoroboric acid, 20 g / L boric acid, 30 g / L stannous fluoroborate, 5 g / L bismuth oxide, and 2 g / L silver oxide; the pH value of the lead fluoroborate plating solution is 1.5;

[0140] S4. Preparation of porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer of aluminum alloy grid: The aluminum alloy grid with Pb-Sn-Bi-Ag alloy intermediate layer was sandblasted on the surface (the sand was silica particles with a particle size of 2.3 mm), placed in a sodium hydroxide solution with a concentration of 70 g / L, and alkaline dissolved for 6 h at a temperature of 50°C. After washing with deionized water, a porous anode grid was obtained. The porous anode grid was used as the anode and the stainless steel plate was used as the cathode. In an alkaline lead plating solution, the stirring rate was 400 rpm and the anode current density was 2 A / dm 2 , the temperature is 50 ℃ for 6 hours, and after washing with deionized water, a porous aluminum alloy grid with cobalt-doped carbon fiber powder-α-PbO2 composite active layer is obtained; the alkaline lead plating solution contains 45g / L lead oxide, 150g / L sodium hydroxide, 200g / L potassium sodium tartrate, 25g / L sodium ethylenediaminetetraacetate, and 10g / L cobalt-doped carbon fiber powder;

[0141] The method for preparing the cobalt-coated carbon fiber powder comprises the following specific steps:

[0142] S41. Carbon fibers (long diameter of 50 μm, short diameter of 2.5 μm) were subjected to degumming treatment by calcination at 400°C, roughening by 20% nitric acid solution for 7 min, sensitization by stannous chloride-hydrochloric acid (12 g / L stannous chloride, 13 ml / L hydrochloric acid) for 7 min, and activation by 13 g / L silver citrate colloid for 3 min to obtain pretreated carbon fibers;

[0143] S42. The pretreated carbon fiber is placed in a cobalt sulfate plating solution and chemically plated with cobalt at a temperature of 60°C for 30 min to obtain a cobalt-coated carbon fiber powder; the cobalt sulfate plating solution contains 12 g / L cobalt sulfate, 17 g / L ethylenediaminetetraacetic acid, 13 g / L sodium hydroxide, 5 mg / L thiourea, and 13 ml / L formaldehyde;

[0144] Compared with the traditional lead alloy positive electrode grid, the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid of this embodiment has a 55% lighter weight, a 39% higher tensile strength, and a 32% higher conductivity.

[0145] The cycle performance diagram of the lead-acid battery of the aluminum-based lead alloy anode grid of this embodiment is shown in FIG. Figure 3 ,from Figure 3 It can be seen that: under the conditions of discharge current 0.5C and 100% DOD, the performance changes of the battery with a rated capacity and voltage of 2V / 2Ah during 100 cycle tests are detected. The cycle period of the lead-acid battery using the aluminum-based lead alloy anode grid of this embodiment is extended by 25%, which can meet the long-term frequent charging and discharging needs of the lead-acid energy storage battery.

[0146] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. An aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid, characterized in that: From the inside to the outside, it is an aluminum alloy substrate, a zinc-antimony impregnated layer (1), a nano-La2O3-doped nickel bottom layer (2), a Pb-Sn-Bi-Ag alloy middle layer (3) and a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer (4).

2. The aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to claim 1, characterized in that: In terms of mass percentage, the aluminum alloy matrix contains 0.2-0.8% Ca, 0.01-0.2% Zr, 0.01-0.1% Ce, 0.01-0.2% Sc, 0.001-0.3% A1-5Ti-B, and the balance is Al; In terms of mass percentage, Sb accounts for 5-10% of the zinc-antimony layer (1), and the remainder is Zn; In terms of mass percentage, the La2O3 in the nano-doped La2O3-nickel bottom layer (2) accounts for 0.2-5%, and the balance is Ni; In terms of mass percentage, the Pb-Sn-Bi-Ag alloy intermediate layer (3) contains 0.5-5.0% Sn. 0.1~1.0%Bi, 0.005~0.1%Ag, the balance is Pb; Calculated by mass percentage, the cobalt-coated carbon fiber powder in the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer (4) accounts for 0.5-5.0%, and the remainder is α-PbO2; calculated by mass percentage of the cobalt-coated carbon fiber powder, Co accounts for 5-20% in the cobalt-coated carbon fiber powder, and the remainder is carbon fiber.

3. The aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to claim 1, characterized in that: The aluminum alloy substrate is a plate-shaped structure, with a pattern pressed on the surface, the pattern depth is 0.05-0.5mm, the pattern width is 0.05-0.3mm, and the cross-sectional thickness is 0.5-6mm; The thickness of the zinc-antimony impregnated layer (1) is 0.5 to 3 μm; the thickness of the nano-La2O3-nickel bottom layer (2) is 3 to 8 μm; the thickness of the Pb-Sn-Bi-Ag alloy intermediate layer (3) is 0.5 to 4 mm; and the thickness of the porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer (4) is 0.1 to 1.0 mm.

4. The method for preparing the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to any one of claims 1 to 3, characterized in that: The specific steps are as follows: S1. Preparation of Zn-Sb layer for immersion plating of aluminum alloy grid: soaking the aluminum alloy grid substrate in an alkaline solution to remove oil, washing with deionized water and placing it in an alkaline zinc-antimony solution for a primary immersion plating reaction, washing with deionized water and placing it in an HNO3 solution for activation, washing with deionized water and placing it in an alkaline zinc-antimony solution for a secondary immersion plating reaction, and washing with deionized water to obtain an aluminum alloy grid with a Zn-Sb layer; S2. Preparation of aluminum alloy grid doped with nano-La2O3-nickel bottom layer: an aluminum alloy grid with a Zn-Sb layer as a cathode and a pure nickel plate as an anode was plated in a neutral nickel plating solution, and the aluminum alloy grid doped with nano-La2O3-nickel bottom layer was obtained by washing with deionized water; S3. Preparation of aluminum alloy grid Pb-Sn-Bi-Ag alloy intermediate layer: using the aluminum alloy grid doped with nano-La2O3-nickel bottom layer as the cathode and the lead-tin alloy plate as the anode, electrodepositing in a lead fluoroborate plating solution, and washing with deionized water to obtain an aluminum alloy grid with a Pb-Sn-Bi-Ag alloy intermediate layer; S4. Preparation of porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer of aluminum alloy grid: The aluminum alloy grid with Pb-Sn-Bi-Ag alloy intermediate layer is subjected to surface sandblasting treatment, placed in a sodium hydroxide solution for alkaline dissolution treatment, and washed with deionized water to obtain a porous anode grid. The porous anode grid is used as the anode and the stainless steel plate is used as the cathode. Electrodeposition is carried out in an alkaline lead plating solution, and the aluminum alloy grid with a porous cobalt-doped carbon fiber powder-α-PbO2 composite active layer is obtained after washing with deionized water.

5. The method for preparing the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to claim 4, characterized in that: Step S1. The alkaline solution is a NaOH-Na2CO3 mixed solution, wherein NaOH 10~40g / L, Na2CO3 20~40g / L; The alkaline zinc antimony solution contains 200-400 g / L NaOH, 60-80 g / L ZnO, 30-80 g / L potassium antimony tartrate, 0.5-2 g / L FeCl3, and 1-3 g / L NaNO3; The mass concentration of HNO3 solution is 20-50%.

6. The method for preparing the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to claim 4 or 5, characterized in that: Step S1. Soaking and degreasing at a temperature of 60 to 80°C for 1 to 5 minutes; The temperature of the primary immersion plating reaction is 30-50°C and the time is 10-60S; Activation time is 10 to 60 seconds; The temperature of the secondary immersion plating reaction is 30-50°C and the time is 10-30S.

7. The method for preparing the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to claim 4, characterized in that: Step S2. The neutral nickel plating solution contains 100-300 g / L nickel sulfate, 10-30 g / L nickel chloride, 100-300 g / L citric acid, 10-60 g / L boric acid, and 5-20 g / L nano-La2O3 powder; the pH of the neutral nickel plating solution is 5-7; The cathode current density of composite plating is 1~5A / dm 2 , temperature is 40-60℃, time is 5-20min.

8. The method for preparing the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to claim 4, characterized in that: Step S3. The lead fluoroborate plating solution contains 100-300 g / L lead acetate, 100-200 g / L fluoroboric acid, 10-30 g / L boric acid, 10-50 g / L stannous fluoroborate, 2-8 g / L bismuth oxide, and 1-3 g / L silver oxide; the pH value of the lead fluoroborate plating solution is 1-2; Anode current density of electrodeposition is 1~5A / dm 2 , temperature is 30~50℃, time is 12~24h.

9. The method for preparing the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to claim 4, characterized in that: Step S4. The concentration of the sodium hydroxide solution is 40 to 100 g / L, the temperature of the alkali treatment is 40 to 60°C, and the time is 4 to 8 hours; Step S4. The alkaline lead plating solution contains 30-60 g / L lead oxide, 100-200 g / L sodium hydroxide, 100-300 g / L potassium sodium tartrate, 10-40 g / L sodium ethylenediaminetetraacetate, and 4-16 g / L cobalt-coated carbon fiber powder; Anode current density of electrodeposition is 1~3A / dm 2 , temperature is 40-60℃, time is 4-8h.

10. The method for preparing the aluminum-based lead alloy / cobalt-doped carbon fiber powder-α-PbO2 composite positive electrode grid according to claim 9, characterized in that: The preparation method of cobalt-coated carbon fiber powder comprises the following specific steps: S41. The carbon fiber was sequentially subjected to calcination to remove the glue, roughening with nitric acid solution, sensitization with stannous chloride-hydrochloric acid, and activation with colloidal silver citrate to obtain pretreated carbon fiber; S42. The pretreated carbon fiber is placed in a cobalt sulfate plating solution for chemical cobalt plating to obtain a cobalt-coated carbon fiber powder; the cobalt sulfate plating solution contains 5-20 g / L cobalt sulfate, 5-30 g / L ethylenediaminetetraacetic acid, 5-20 g / L sodium hydroxide, 0.2-10 mg / L thiourea, and 5-20 ml / L formaldehyde.

Citation Information

Patent Citations

  • Decoration method for attaching lead oxide on surfaces of carbon fibers

    CN109306621A

  • Lead storage battery capable of overcoming early capacity attenuation and preparation method thereof

    CN110364770A

  • Gradient composite lead dioxide anode plate and preparation method and application thereof

    CN113293411A

  • Long-service-life light composite positive plate grid and preparation method thereof, and positive electrode plate and preparation method thereof

    CN113394408A

  • Titanium-based gradient lead dioxide composite electrode material for copper electrodeposition and preparation method thereof

    CN113862759A

Cited By

  • Positive plate of lead-acid battery as well as preparation method and application of positive plate

    CN120933370A